Jaime Hayon works. - Hayon, Jaime, ....- (Berlin : Gestalten, 2008)
The Spanish designer and artist Jaime Hayon is a rising star in the international creative scene. It's safe to say that he will be one of the most influential designers in the years to come. Hayon embodies a new type of creative Renaissance man, who ?????? thanks to his interdisciplinary approach and extraordinary talent ?????? can realize his unique stylistic language across various areas and media. Whether he is creating interior design, furniture, illustration, tableware or decorative vases and ceramics, Hayon's signature style always shines through. Seemingly without effort, his designs coherently bring together diametrical opposites such as opulence and practicality, sensuality and precision as well as finesse and restraint. This first monograph about Jaime Hayon presents the full spectrum of his work. The book features projects such as his extensive ceramic installation for Bisazza in Milan and the interior design for La Terraza del Casino, an exclusive restaurant in central Madrid, as well as designer toys and furniture, including his awardwinning bathroom collection, AQHayon. Ranging from clear and harmonious to playfully extravagant, all of the examples attest to his inimitable grasp of form, style and colour. In addition to his impressive body of work, which also includes his collaborations with international clients such as Camper, Swarovski and Lladr????, the book contains new personal projects, sketches, illustrations and productions. Documented by the photographer Nienke Klunder, these previously unpublished works have been exclusively created for Jaime Hayon Works and show facets of Hayon's talent that are revealed here for the first time.